SOCIO-CULTURAL CHALLENGES OF MISINFORMATION - Shadiuk, Tamara (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
information and false knowledge, which has huge dissemination in society and causes permanent multifaceted challenges. In this paper, misinformation is understood as types of information that lead to a misperception of the actual state of things in the world. The essence of misinformation as untruth, false knowledge is analyzed on the example of the phenomenon of "conspiracy theory". Research methods. The research methods used in the paper are analytical, system-logical, dialectical, and synthetic. As interdisciplinary approach synthesizes the achievements of the socio-philosophical direction of such fields as psychology, sociology, epistemology, ethics, and culture studies, its application determines the need for research the essential characteristics of "conspiracy theory" as a kind of misinformation. The aim and tasks. This article aims to analyze the scientific approaches concerning the essence of the phenomenon of misinformation, particularly, "conspiracy theory" as its variety, as well as to establish socio-cultural assessments of challenges and potential consequences of information boom, which is likely to contain false information. In the context of this goal, the main tasks of this paper are to introduce the general and individual approaches concerning the analysis of the misinformation phenomenon, define the concepts "conspiracy theory", "conspiracism" and "conspiratorial worldview", as well as reveal problematic aspects of cognitive, epistemic, and ethical measurements of "conspiracy theory". Research results. It is claimed that in the socio-cultural aspect, there is a general manipulation of public consciousness, in which misinformation is used as an ideological tool for speculative political purposes, that is accompanied by populism and propaganda. At the individual level, the situation is problematized due to internal effects or attitudes of thinking, substantiated by the cognitive sciences as intellectual cognitive biases. The main biases are the lack of meta-knowledge, confirmation, and confabulation, which provoke such challenges as devaluation and rejection of professional expert and scientific knowledge, and as a result the establishment of ignorance and narcissism cult. Discussion. "Conspiracy theory" as a misinformation phenomenon is based on the world-view conspiracy. It is an example of communicative problems that influence the political and socio-economic situation in society. "Conspiracy theory" is understood as one of the epistemic errors that arise due to dissatisfaction with the basic epistemic needs - understanding and cognitive interest. Epistemic distortions, errors, vices, and biases are a complex cognitive problem that reveals a defective way of thinking and inappropriate, including indifferent, attitude to knowledge. Conclusion. The social and individual levels of the phenomenon of disinformation are based on moral and epistemological contexts.In general, the socio-cultural situation is defined as a communicative crisis: a crisis of trust and understanding, loss of dialogue.